Major insect pests of tea plant (Camellia sinensis) in Iran - Saber Hamishegi, Maryam; Hajizadeh, Jalil; Ramzi, Samar (Journal of Biological Studies, 2024)
An extensive survey was carried out during 2022-2023 for collection and identification of insect pests associated with tea plant in Guilan province, North of Iran. A total of 10 species belonging to nine genera and eight families were identified. Considering the species spectrum, the order Hemiptera has been reported as the most prevalent insect order with seven species followed by Thysanoptera (with two species) and Orthoptera (with one species). Out of 10 species of insects reported Toxoptera aurantii (Boyer de Fonscolombe), Pseudococcus viburni (Signoret), Pulvinaria floccifera (Westwood), Pulvinaria aurantii (Cockerell), Thrips hawaiiensis (Morgan) and Heliothrips haemorrhoidalis (Bouché) have been identified as the predominant species and therefore considered as the pests of major importance. All identified species except T. aurantii, P. floccifera and P. viburni appeared new to tea gardens of the Guilan province. An alphabetic list of the identified insect pest species and collection information has been provided.